The Impact of Government Financing Programs And Liquidity On Purchasing Power - Pijar Lintang Alit; Egi Dwi Purnomo; Achmad Luthfi Tunggul Baroto; Annisa Sabila Rizqi; Agustin Yudi Pratama (Jurnal Pallangga Praja (JPP), 2026)
This research examines the Indonesian government's role in implementing quasi-fiscal policies through Government Financing Programs and liquidity management, as well as macroeconomic constraints that affect public purchasing power. The data used in this study is a distribution of data from 34 Indonesian provinces between 2017 and 2024. The results indicate that the implementation of Program pembiayaan pemerintahs and additional liquidity can increase public purchasing power. Meanwhile, macroeconomic challenges, in this case, the poverty rate in a region, can hinder the growth of public purchasing power.